GREEN protocol: gradient based energy efficient routing with network coding capacity - Nawaz, F. (Springer New York LLC, 2016)
A fundamental challenge in the acceptability of Wireless SAW Sensor Network (WSSN) for industrial applications, is to enhance the lifespan and packet delivery ratio (PDR) of the network. This work proposes a routing protocol for WSSN that selects the best neighbours for data forwarding and employs network coding to provide reliable and energy efficient data delivery. The proposed algorithm improves the lifetime of industrial wireless mesh and star mesh networks. Energy efficiency increases as more data is routed towards the sink with less number of transmissions. Performance metrics including latency, PDR and throughput have been investigated to prove the effectiveness of the proposed routing protocol. The proposed routing protocol is particularly suited to the needs of dense reader environment deployed in an industrial environment, where the sensors are passive and have a limited transmission range. The protocol is applicable to long term passive sensor network and operates in an unattended environment. Â© 2015, Springer Science+Business Media New York.